Trypanosoma cruzi loop-mediated isothermal amplification (Trypanosoma cruzi Loopamp) kit for detection of congenital, acute and Chagas disease reactivation - Besuschio, Susana A (2020)
Fil: Besuschio, Susana A. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor Torres". Laboratorio de Biología Molecular de la Enfermedad de Chagas; Argentina